Reviewing Students’ Vocabulary Mastery By Using Kahoot At Holmesglen Partnering With University of Muhammadiyah Tangerang - Muhammad Abduh Almanar (Universitas Muhammadiyah Kalimantan Timur, 2019)
The present study investigated the use of Kahoot as the free game-based learning platform which provided the students with ongoing feedback on their learning progresses. Reviewing the students’ vocabulary was the focus of this study. Unlike summative test that tended to have formal assessment, Kahoot provided a learning with engagement and responsive feedback both students and teacher. In term of student’s vocabulary mastery, Kahoot was the learning model of this study. Blended learning was applied technically in this study so that the students’ vocabulary mastery was reviewed and tested through the application of Kahoot accessed by students’ mobile phones. The methodology of this study was based on a questionnaire survey that was conducted to determine the use of Kahoot to the students’ vocabulary mastery. More detail information was also added through observation, field note and interview. The 20 students of UMT (University of Muhammadiyah Tangerang) from Holmesglen English class were the population and samples of this study.